Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors